Steam explosion and sequential steam explosion - dilute acid pretreatment optimization of banana pseudostem for polyhydroxybutyrate (PHB) production - Mabazza, Kristel Anna A.; Ventura, Jey-R S.; Nayve, Jr., Fidel Rey P.; Requiso, Princess J.; Alfafara, Catalino G. (2020)
Polyhydroxybutyrate (PHB) is a suitable biodegradable alternative to non-renewable petroleum-based plastics. Readily available agricultural lignocellulosic residues such as banana pseudostem can be utilized as a substrate to reduce the production cost of PHB and improve its feasibility for commercialization. Accordingly, pretreatment of banana pseudostem is needed to efficiently convert the substrate to PHB. In this study, optimization of two pretreatment methods for banana pseudostem ? namely, steam explosion and sequential steam explosion ? dilute acid pretreatment ? were optimized to improve the digestibility of the biomass and consequently increase the production of reducing sugars in the hydrolysate during enzymatic saccharification. Response surface methodology (RSM)-designed experiments showed that among all factors investigated, for both pretreatment methods, the steam explosion temperature had the strongest positive impact on reducing sugar production. Optimum conditions of steam explosion pretreatment were 219.31 °C steam explosion temperature and 10 min of pretreatment time, producing 7.33 g/L (48.87% yield) of reducing sugars in the enzymatic hydrolysate. For sequential pretreatment, optimum conditions were 220 °C steam explosion temperature, 135 °C dilute acid temperature, 44 min of dilute acid reaction time, and 1.57% w/v H2SO4, with a corresponding reducing sugar concentration of 13.02 g/L (86.79% yield). A 90% increase in reducing sugar yield was observed after dilute acid pretreatment of steam-exploded banana pseudostem. Using the hydrolysate from sequentially-pretreated banana pseudostem, PHB (2.64 g/L) was successfully synthesized after 12 h of bacterial fermentation. Hence, sequential pretreatment was proven effective in producing enzymatic hydrolysates from banana pseudostem for PHB production. (Author's abstract)